Ubiquitin-specific protease 10 determines colorectal cancer outcome by modulating epidermal growth factor signaling via inositol polyphosphate-4-phosphatase type IIB - Kubaichuk, Kateryna; Seitz, Timo; Bergmann, Ulrich; Glumoff, Virpi; Mennerich, Daniela; Kietzmann, Thomas (SPRINGERNATURE, 2025)
Although there have been advances in understanding colorectal cancer (CRC) pathogenesis, significant gaps still exist, highlighting the need for deeper insights. Dysregulated protein homeostasis, including perturbations in the epidermal growth factor receptor (EGFR) pathway, remains a focal point in CRC pathogenesis. Within this context, the roles of ubiquitin ligases and deubiquitinases have attracted attention, but exploration of their precise contributions is still in its early stages. To address this gap, we investigated the involvement of the deubiquitinase USP10 in CRC. Our in vitro and in vivo study reveals a new paradigm in CRC biology and unravels a novel mechanistic axis, demonstrating for the first time the involvement of inositol polyphosphate 4-phosphatase type II B (INPP4B) in USP10-mediated CRC modulation. Specifically, our study demonstrates that the loss of USP10 results in reduced sensitivity to the EGFR tyrosine kinase inhibitors gefitinib and osimertinib. This is accompanied by a decrease in the activation of the AKT1/PKB pathway upon EGF stimulation, which is mediated by INPP4B. Importantly, in vivo xenograft experiments validate these findings and highlight the crucial role of USP10, particularly in conjunction with INPP4B, in driving CRC progression. The findings enhance our understanding of CRC pathobiology and reveal a new regulatory axis involving USP10 and INPP4B in CRC progression. This unique insight identifies USP10 and INPP4B as potential therapeutic targets in CRC.